2024
DOI: 10.24018/ejmed.2024.6.1.2032
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns and Metabolic Syndrome Risk in Adults Living with HIV: A Cross-Sectional Study in Lusaka District, Zambia

Peryson Kekelwa Kalaluka,
Anatolii Tsarkov,
Petro Petlovanyi
et al.

Abstract: Background: Metabolic syndrome, a cluster of cardiovascular risk factors, affects approximately 25% of the global population, with a significant impact on the 37,900,000 people living with HIV in 2017. Objective: This cross-sectional study (April-July 2020) in Lusaka District aimed to assess dietary patterns and metabolic syndrome risk in 180 randomly sampled HIV-positive individuals (aged 18 and above) from three health facilities. Methods: Participants underwent anthropometric measurements, blood pressure ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…A significant randomized controlled study demonstrated that dietary strategies could effectively reduce key cardiometabolic risk factors in PLHIV undergoing ARV therapy, impacting hypertension, blood glucose levels, and lipid profiles positively [17], [23], [24].…”
Section: Introductionmentioning
confidence: 99%
“…A significant randomized controlled study demonstrated that dietary strategies could effectively reduce key cardiometabolic risk factors in PLHIV undergoing ARV therapy, impacting hypertension, blood glucose levels, and lipid profiles positively [17], [23], [24].…”
Section: Introductionmentioning
confidence: 99%
“…Self-Efficacy and Determinants of Newborn Resuscitation Practices the mental well-being and operational capacity of healthcare providers [8]. Dietary and lifestyle factors play a significant role in health outcomes [9], [10]. Similarly, providing comprehensive support and resources to healthcare professionals can significantly enhance their self-efficacy and effectiveness in clinical procedures [11].…”
Section: Introductionmentioning
confidence: 99%